The Mississippi and the making of a nation : from the Louisiana Purchase to today - Ambrose, Stephen E; Brinkley, Douglas (Washington, D.C. : National Geographic, 2002)
An exploration of the Mississippi River, tracing its length from Minnesota to the Gulf of Mexico, and discussing its important role in the history of the United States. Includes photographs, period illustrations, artwork, documents, and maps
Head of passes -- New Orleans -- Portfolio : the delta -- River road plantations -- Natchez -- Portfolio : the Old South -- The delta : from Vicksburg on -- Memphis -- Portfolio : the river in flood -- The great confluence -- St. Louis -- Portfolio : the Delta Queen -- Mark Twain country -- The quad cities and Dubuque -- Portfolio : the headwaters -- Minnesota
Includes bibliographical references (p. 267-268) and index
Keywords: Frontier and pioneer life -- United States; Mississippi River -- History; Mississippi River Valley -- History; West (U.S.) -- History; United States -- Territorial expansion